Pluriversal futures for design education - Noel, Lesley-Ann; Ruiz, Adolfo; van Amstel, Frederick M. C.; Udoewa, Victor; Verma, Neeta; Botchway, Nii Kommey; Lodaya, Arvind; Agrawal, Shalini (My University, 2023)
The Future of Design Education working group on pluriversal design—with members from Latin America, the Caribbean, Africa, South and Southeastern Asia, North America, Oceania, and Europe—developed recommendations for higher education design curricula. The group addresses the dominance of a Eurocentric design canon and worldwide colonization by a twentieth-century design monoculture grounded in the concept of universal human experience. Curricular recommendations honor Indigenous worlds and place-based ways of being, and chime with anthropologist Arturo Escobar’s premise that every community practices the design of itself, through participatory processes that are independent of experts. The authors posit that rather than a Cartesian rationalist perspective, the group advocates a relational view of situations in which the design responses to interdependent natural, social, economic, and technical systems, are specific to places and cultures. The recommendations assert a pluriversal design imperative in which multiple worldviews thrive and diverse lived experiences inform the entire field, as well as individual projects.
Keywords: pluriverse; pluriversal design; ontological design; relationality; lived experience; decolonizing design